부식 식도염 후에 발생한 암육종 - 옥주현; Ju Hyun Oak; 정우철; Woo Chul Chung; 정지한; Ji Han Jung; 김진동; Jin Dong Kim; 이정록; Jeong Rok Lee; 백창렬; Chang Nyol Paik; et al. (The Korean journal of gastroenterology, 2008)
Carcinosarcoma of the esophagus is a rare malignancy accounting for approximately 1-2% of all esophageal neoplasms. It presents as a bulky intraluminal polypoid lesion mainly in the mid to lower esophagus, which harbors both carcinomatous and sarcomatous components histologically. It often presents relatively early because of its rapid intraluminal growth. We report the case of a 69-year-old man who had suffered from dysphagia for 1 month. He was previously admitted to the hospital due to corrosive esophagitis caused by ingestion of acetic acid. Endoscopy and radiological studies revealed a bulky polypoid mass with superficial ulcerations and mucosal friability, measuring 10 cm in length approximately, in the mid-esophagus. Subtotal esophagectomy with esophagogastrostomy was done. Microscopically it was composed of sarcomatous component intermingled with squamous cell carcinoma. Immunohistochemical stains reveal cytokeratin, 34βE12, and p63 positivity in the nests of carcinoma, and desmin and vimentin positivity in the spindle cells of sarcomatous stoma. (Korean J Gastroenterol 2008;52:42-47)